Multi-Stakeholder Partnership in the Implementation of Stunting Reduction Acceleration Policies: A Synthesis of Systematic Literature Review - Nur Alifah; Indah Ayu Permana Pribadi; Chamid Sutikno; Ariesta Amanda (GoAcademica Research & Publishing, 2026)
Stunting remains a complex public health problem in many developing countries, including Indonesia, requiring integrated policy approaches involving multiple sectors and actors. This study aims to synthesize existing literature on the implementation of stunting reduction policies through a multi-stakeholder partnership approach using a Systematic Literature Review (SLR). The study follows the PRISMA framework to ensure a systematic, transparent, and replicable selection process. Literature was retrieved from Scopus, Web of Science, and other indexed databases using predefined search strings related to stunting, government policy, policy implementation, and collaborative governance. A total of 1,690 records were initially identified, of which 52 studies met the inclusion criteria after screening, eligibility assessment, and full-text review. The selected studies were analyzed using thematic synthesis and bibliometric mapping using VOSviewer to identify key themes and research trends. The synthesis results indicate that stunting reduction policies are predominantly implemented through integrated health and nutrition interventions. However, their effectiveness is strongly influenced by policy implementation capacity, cross-sector coordination, and governance structures. The multi-stakeholder partnership approach plays an important role in facilitating collaboration among government institutions, health workers, non-governmental organizations, academics, the private sector, and communities. Despite this, implementation challenges remain, including fragmented governance, limited resources, and disparities in institutional capacity across regions. Bibliometric analysis also shows that governance-related concepts are less dominant compared to health-oriented studies. This study concludes that stunting should be understood not only as a health issue but also as a policy implementation and governance challenge requiring stronger multi-actor collaboration. The study contributes to the literature by synthesizing fragmented evidence on policy implementation and multi-stakeholder partnerships in stunting reduction.